Perfil socioeconômico, obstétrico e clínico de mulheres gestantes HIV positivas: os casos de uma maternidade de referência em Fortaleza–CE - Saunders, Anuzia Lopes (2023)
This work aimed to describe the socioeconomic, obstetric and clinical profile of HIV-positive pregnant women in a reference maternity hospital in Fortaleza - CE. Methodology: A descriptive, cross-sectional epidemiological study carried out in a tertiary reference maternity hospital in 2020. The study population consisted of pregnant women diagnosed with HIV. Data collection was through interviews with the aid of a structured and consolidated questionnaire in the Google Forms tool. The presentation of data is through graphs and tables, divided into 3 thematic axes: socioeconomic data, obstetric profile and clinical situation of HIV infection. Results: 75 pregnant women were interviewed, of which 33.3% were from Fortaleza and the others from the interior of the state. 62.7% were between 18 and 30 years old, the majority of mixed race/color, with complete primary education and stable union without formalization, the main source of income is through social programs. At the time of the interview, 49.3% of the pregnant women were in the 2nd trimester of pregnancy, 82.7% were multiparous, 64% had between 1 and 2 children and 34.6% of the pregnant women were at increased risk for obstetric complications. The most desired mode of delivery among the interviews was the vaginal route with 56%. Of those surveyed, 64% had already been diagnosed with HIV infection before the current pregnancy, of which 45.8% were diagnosed in the previous pregnancy. In sharing the diagnosis with the sexual partner, 89.3% had already shared the serology with the partner, 76% were aware of the serological condition of the partner and of these 35.1% have positive serology for HIV. It was observed that 65% of the patients had a connection with the maternity and a specialized care service. In the clinical conditions of the interviewees, more than half, 52.4%, had a good CD4 cell count and 76.3% had an undetectable viral load, we emphasize that these data are not expressive, since less than half of the women had both exams recorded in their medical records. 64% of the interviewees were already using drug therapy. Twenty-one women started ART in the current pregnancy, of which 52.4% between the 13th and 20th gestational week. Another 6 pregnant women were still waiting for a prescription to start therapy. Only 37.5% received guidance on safe reproductive planning. Conclusion: We conclude that HIV/AIDS prevention policies in women should still be concentrated in the pre-conception period, offering periodic exams, and guidance on harm reduction, as we identified that there are still flaws in early diagnosis. Another important point is the clinical management of pregnant women with the diagnosis; guiding them regarding safe conception, reducing the risk of vertical transmission, empowering them to carry out safe and healthy pregnancies, in addition to guaranteeing prenatal care with timely exams and treatment. This is the only way we will stop the transmission chain and achieve the desired indicators of eliminating vertical transmission of HIV, considering that this problem is preventable when the necessary and timely conditions are offered for the mother and her child.